EVIDENCE MATTER: INSTRUMENTALIZATION AND EXPOSURE OF THE FEMALE BODY IN THE ERA OF TECHNOLOGY (PERcursos Linguísticos, 2020)
This article aims to present a brief discussion about the cult of the body in the age of technology, especially in the online universe. In a scenario full of technological devices and social networks, which facilitate the dissemination of images and provide body display, this becomes a showcase that, often, reflects an excessive concern with body aesthetics, and can therefore generate serious consequences for women's lives. Thus, discussions about bodies, especially female bodies that are constantly on display in virtual spaces, and the discourses that compose and affect them, become increasingly necessary. Thus, in order to understand this phenomenon in practice, we used Foucault (2014), to carry out an analysis of the network of enunciations produced about the body from a photo published in December 2019 by the actress and singer Cleo Pires, in her profile. Instagram, wearing a bikini that partially showed her body, which generated great repercussion and numerous criticisms. The publication had more than one million likes and about 24 thousand comments. Furthermore, we used concepts from authors such as Novaes (2006), Goldenberg (2002) and Ortega (2008) to compose the framework used here.